Lentivirus-Carried microRNA-195 Rescues Memory Deficits of Alzheimer's Disease Transgenic Mouse by Attenuating the Generation of Amyloid Plaques - Dan Su; Yani Chai; Junkai Yang; Xuqiao Wang; Ying Liu; Jing Ma; Xin Tang; Chandan Mishra; Shah Ram Chandra; Weidong Yue; Jing Ai (Frontiers Media S.A., 2021)
Although lots of new drugs are developed to treat Alzheimer's disease (AD), many clinical trials of monotherapy have failed to affect disease progression or symptoms compared with placebo. Recently, scientists believe that combination treatment is more promising than monotherapy. Previous studies found that microRNA-195 (miR-195) was down-regulated in the hippocampi and cortices of chronic brain hypoperfusion (CBH) rats and ApoE4(+/+) mice, and up-regulation of miR-195 can improve the declined cognitive function of ApoE4(+/+) mice and CBH rats by targeting multi-genes that are related to AD pathology, including amyloid precursor protein (APP) and β-site APP cleaving enzyme 1 (BACE1) genes. However, whether the gain-of-function of miR-195 could improve the impaired learning and memory ability of APP/PS1 transgenic mouse has not been reported. In this study, we stereotaxically injected lentiviral-carried miR-195 into the bilateral hippocampus of 4-month-old (4M) APP/PS1 mice. Morris water maze (MWM) was performed to detect the effect of miR-195 on the cognitive function of APP/PS1 mice after 1M, 2M, and 3M treatment. Western blot was used to detect the expression of APP, BACE1, and AT8. Aβ plagues were quantitatively assessed by immunofluorescence technique. We found that the declined cognitive phenotype of APP/PS1 mice occurred at the age of 6M, not at the age of 5M. And treatment of Lv-pre-miR-195 to APP/PS1 mice for 1M did not achieve any changes. Although Lv-pre-miR-195 treatment for 2M improved the declined learning ability of APP/PS1 mice, it did not affect the memory functions. However, Lv-pre-miR-195 treatment in APP/PS1 mice for 3M can effectively improve both the learning and memory ability of APP/PS1 mice at the age of 7M. Further studies demonstrated that gain-of-function of miR-195 by Lv-pre-miR-195 injection could inhibit the increased APP and AT8 expression of APP/PS1 mice but did not affect BACE1 level that was not changed in both hippocampus and cortex. By counting the number of Aβ plaques of different sizes, we found that Lv-pre-miR-195 treatment mainly reduced the number of Aβ plaques of less than 20 μm, but did not affect the number of Aβ plaques of greater than 50 μm. Taken together, the gain-of -function of miR-195 in the hippocampus can improve the cognition of APP/PS1 mice, probably by blocking the formation of Aβ plagues rather than clearing those that have already formed Aβ plagues.